Islam, secularism, and liberal democracy : toward a democratic theory for Muslim societies - Hashemi, Nader, 1966- (Oxford University Press, 2009)
"Islam's relationship to liberal-democratic politics has emerged as one of the most pressing and contentious issues in international affairs. Nader Hashemi challenges the widely held belief among social scientists that religious politics and liberal-democratic development are structurally incompatible. While there are certainly tensions between religion and democracy, the two are not irreconcilable." "Liberal democracy requires a form of secularism to sustain itself, yet the main political, cultural, and intellectual resources that Muslim democrats can draw upon are religious. How can this paradox be reconciled? Hashemi makes three principal arguments. First, in societies where religion is a key marker of identity, the road to liberal democracy must pass through the gates of religious politics. The process of democratization, therefore, cannot be artificially de-linked from debates about the normative role of religion in government. Second, while liberal democracy requires secularism, religious traditions are not born with an inherent secular and democratic conception of politics. These ideas must be developed, and in an emerging democracy, how they are developed is critical. Finally, Hashemi argues that there is an intimate relationship between religious reformation and political development. While the former often precedes the latter, these processes are deeply interlinked. Democratization does not require a privatization of religion, but it does require a reinterpretation of religious ideas that are conducive to liberal democracy. By engaging in this reinterpretation, religious groups can playa central role in the development and consolidation of democracy."